Economic Growth in the European Union c - Nikas, Christos; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2020)
This book studies the economic recovery of individual European Union member states more than ten years after the beginning of the global economic crisis. In light of austerity policies and conservative government investments in many EU countries, it explores how higher growth rates can be achieved by stimulating firms and economic sectors with a high accelerator potential. The contributing authors analyze the effects of EU policies on small and medium-sized enterprises (SMEs), while also studying EU policies with the potential to foster investments and economic growth. Furthermore the book assesses the EU policy on foreign direct investment (FDI) in the member states, in comparison with similar policies in Russia and the US. The authors demonstrate that FDI, besides providing financial resources, can facilitate modernization especially in the high technology sectors. Finally, the book provides a sector analysis and policy recommendations on tourism and immigration, as well as economic protectionism, since tourism has proved to be the most dynamic sector, especially in the European South, while immigration is one of the most serious issues the EU is currently facing. This book will appeal to scholars in economics and related fields, as well as decision-makers and professionals at governmental institutions looking for policy measures and tools to stimulate economic growth.
Part 1: International Growth Concerns -- Economic Nationalism: Constrained and Fragmented, if any? -- Digitalization: Disrupting the Business Models of Multinationals -- Part 2: EU Policies for Growth -- EU Corporate Governance Framework; The Role of the EU Institutions -- The EU Digital Single Market and the Platform Economy -- SMEs and State Aid -- Funding from EU Structural Funds Towards SMEs: Findings and Suggestions on Increasing SMEs Financial Capacity -- EFSI 2.0: The Extension and Enhancement of the European Fund for Strategic Investments as a Case Study for the Review of European Policies -- Foreign Direct Investment and Growth Causality in the EU Countries and in the Transition Economies -- Part 3: Country Specific Analyses on Foreign Direct Investment and Economic Growth -- FDI to and from the Russian Federation: A Case Study of the Western Balkans and the Role of the EU -- Sovereign Debt Crisis in Greece and its Relation with Foreign Direct Investment and Competitiveness in Greece -- Sector Analysis and Economic Growth in Greece. Domination of Tourism Over Other Sectors -- Immigration and Economic Growth: The Case of Greece.
Keywords: Economic growth; Political economy; Small business; Economic policy; Economics; European Union; Economic Growth; International Political Economy; Small Business; Economic Policy; Political Economy/Economic Systems; European Union Politics